1-D Vision: Encoding of Eye Movements by Simple Receptive Fields. (August 2015) - Ahissar, Ehud; Ozana, Shira; Arieli, Amos
Eye movements (eyeM) are an essential component of visual perception. They allow the sampling and scanning of stationary scenes at various spatial scales, primarily at the scene level, via saccades, and at the local level, via fixational eyeM. Given the constant motion of visual images on the retina, a crucial factor in resolving spatial ambiguities related to the external scene is the exact trajectory of eyeM. We show here that the trajectory of eyeM can be encoded at high resolution by simple retinal receptive fields of the symmetrical type. We also show that such encoding can account for motion illusions such as the Ouchi illusion. In addition, encoding of motion projections along horizontal and vertical symmetrical simple retinal receptive fields entails a kind of Cartesian decomposition of the 2-D image into two 1-D projections.